La chronique sonore d’une grève par les grévistes : décembre 1966 – février 1967 aux Avions Marcel Dassault (Bordeaux) - Noëlle Gérôme (Transposition)
During a long strike at the Dassault-Aviation factories in Martignac and Merignac (from 1 December 1966 to 28 February 1967), workers from the inter-union coalition recorded their songs and one of the soundmarks of the demands, the “tam-tam” which echoed in the workshops to the hammered rhythm of “Das-sault doit pa-yer”. The preservation of these rare testimonies, which attest to the importance of sound and musical expression during the strike action, was ensured by the self-release of a commemorative 33-rpm vinyl, Les fruits de la colère, where the in vivo recordings are integrated into a chronological account of the struggle. Noëlle Gérôme, an ethnologist in the French field at the CNRS, transcribed and analysed the entire document in 1986 for the journal Technologies, Idéologies, Pratiques, and in 1999 she used an extract from it in the proceedings of a symposium of the Société d’Ethnologie Française. She presented the socio-political significance of symbolic worker productions, the richness of sound cultures within factories and the skills of their personnel when it comes to producing and recording their sound universe beyond their professional functions. Revised by the author in an unpublished form, this online republication offers the reader access to the entire audio document.